The Effectiveness of Using Domino Puzzles as A Learning Medium to Improve Abilities Counting Students - Bogy Restu Ilahi; Meilida Eka Sari; Susanto, Edy; Putri Milanda Bainamus (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Mathematics learning at the elementary school level plays a strategic role in developing students' logical, creative, and critical thinking skills. However, many students still face difficulties in understanding number concepts and performing basic operations such as addition, subtraction, multiplication, and division. This study aims to determine the effectiveness of Domino Puzzle-based learning media in improving the arithmetic skills of fifth-grade students at SD Negeri 51 Bengkulu. This research used a pre-experimental design with pre-test and post-test on 30 students using 10 evaluation questions. Data were analyzed using the N-Gain formula. The results show an average N-Gain score of 0.81, which falls into the high category, indicating that this learning media is effective in enhancing students' arithmetic skills. This media not only improves calculation skills but also supports students' motivation, engagement, and conceptual understanding. Therefore, the sustainable application of Domino Puzzle media is recommended to strengthen mathematics learning achievement in elementary schools. Keywords: Domino Puzzle, Arithmetic Skills, Elementary School. Abstrak: Pembelajaran matematika di tingkat sekolah dasar memegang peran strategis dalam membentuk keterampilan berpikir logis, kreatif, dan kritis siswa. Namun, banyak siswa masih mengalami kesulitan dalam memahami konsep bilangan dan melakukan operasi dasar seperti penjumlahan, pengurangan, perkalian, dan pembagian. Penelitian ini bertujuan untuk mengetahui efektivitas media pembelajaran berbasis Domino Puzzle dalam meningkatkan kemampuan berhitung siswa kelas V SD Negeri 51 Bengkulu. Metode yang digunakan adalah pra-eksperimen dengan desain pre-test dan post-test pada 30 siswa, menggunakan 10 soal evaluasi kemampuan berhitung. Analisis data dilakukan dengan rumus N-Gain. Hasil penelitian menunjukkan bahwa nilai rata-rata N-Gain sebesar 0,81, termasuk kategori tinggi, yang menunjukkan bahwa media pembelajaran ini efektif dalam meningkatkan kemampuan berhitung siswa. Media ini tidak hanya memperkuat keterampilan berhitung, tetapi juga mendukung motivasi, keterlibatan, dan pemahaman konsep siswa. Oleh karena itu, penerapan media Domino Puzzle secara berkelanjutan dianjurkan untuk memperkuat pencapaian pembelajaran matematika di sekolah dasar. Kata kunci: Domino Puzzle, Kemampuan Berhitung, Sekolah Dasar.